(untitled) (Clinics, 2021)
OBJECTIVE: To investigate the effects of exercise training (ET) on muscle sympathetic nerve activity (MSNA) and executive performance during Stroop Color Word Test (SCWT) also referred to as mental stress test. METHODS: Forty-four individuals with obstructive sleep apnea (OSA) and no significant co-morbidities were randomized into 2 groups; 15 individuals completed the control period, and 18 individuals completed the ET. Mini-mental state of examination and intelligence quotient were also assessed. MSNA assessed by microneurography, heart rate by electrocardiography, blood pressure (automated oscillometric device) were measured at baseline and during 3 min of the SCWT. Peak oxygen uptake (VO2 peak) was evaluated using cardiopulmonary exercise testing. Executive performance was assessed by the total correct responses during 3 min of the SCWT. ET consisted of 3 weekly sessions of aerobic exercise, resistance exercises, and flexibility (72 sessions, achieved in 40±3.9 weeks). RESULTS: Baseline parameters were similar between groups. Heart rate, blood pressure, and MSNA responses during SCWT were similar between groups (p>0.05). The comparisons between groups showed that the changes in VO2 (4.7±0.8 vs -1.2±0.4) and apnea-hypopnea index (-7.4±3.1 vs 5.5±3.3) in the exercise-trained group were significantly greater than those observed in the control group respectively (p<0.05) after intervention. ET reduced MSNA responses (p<0.05) and significantly increased the number of correct answers (12.4%) during SCWT. The number of correct answers was unchanged in the control group (p>0.05). CONCLUSIONS: ET improves sympathetic response and executive performance during SCWT, suggesting a prominent positive impact of ET on prefrontal functioning in individuals with OSA. ClinicalTrials.gov: NCT002289625.